Approach towards total knee arthroplasty in Brazil: cross-sectional study - Almeida, Raul Frankllim de Carvalho (2009)
CONTEXT AND OBJECTIVE: Total knee arthroplasty (TKA) has evolved particularly since the 1970s, with improvements in implants and surgical instruments, and has thus become an effective intervention for treating knee arthrosis. Many studies have presented rates of satisfactory clinical and radiological results greater than 90%, from follow-ups of over ten years. Nevertheless, despite scientific evidence showing the efficacy of TKA, the approaches taken present controversies in certain respects. The objective of this study was to evaluate how the Brazilian orthopedists deal with TKA, with investigation of the main aspects of this procedure. DESIGN AND SETTING: Cross-sectional survey conducted during the 39th Brazilian Congress of Orthopedics and Traumatology, in São Paulo, Brazil, in November 2007. METHODS: We applied a questionnaire to orthopedists registered at the congress. The questionnaire was randomly distributed and participation was voluntary; 858 completed questionnaires were included in the analysis. RESULTS: Most of the Brazilian orthopedists were members of SBOT and worked in the southeastern region. They used imported cemented implants through an anterior access route centered on the patella, with replacement of the joint surface of the patella and preservation of the posterior cruciate ligament. They did not have experience with simultaneous bilateral TKA. Postoperatively, they used antibiotics and suction drains for 48 hours. There was no consensus regarding prophylaxis for venous thromboembolism or the frequency of the main complications. CONCLUSION: The majority of Brazilian orthopedists work in the southeastern region of the country and agree about the main aspects of the approaches towards TKA.